Design of suburban bus route for airport access. Issue 6 (3rd July 2017) - Chen, Jingxu; Wang, Shuaian; Liu, Zhiyuan; Wang, Wei
ABSTRACT: Suburban bus routes usually serve a city's peripheral areas with sparse density of travel demand. The distribution of many suburban trips is many-to-one, with all the passengers bound for a common destination like an airport. This paper proposes a methodology for the optimal design of a suburban bus route for airport access, with the objective of minimizing the total access time. Its decisions are the selection of pickup locations from candidate stops and the corresponding visiting sequence. We first consider a special model which is polynomially solvable, and then develop a dynamic programming approach to address this special case. Later, we formulate a generic model and prove it to be NP-hard. Apart from the dynamic programming approach, an artificial bee colony (ABC) approach is developed for good-quality solutions of the practical-size problem. Finally, case studies are carried out to validate the applicability of the proposed models and solution methods.